2007
DOI: 10.1038/ni1476
|View full text |Cite
|
Sign up to set email alerts
|

Allelic 'choice' governs somatic hypermutation in vivo at the immunoglobulin κ-chain locus

Abstract: Monoallelic demethylation and rearrangement control allelic exclusion of the immunoglobulin kappa-chain locus (Igk locus) in B cells. Here, through the introduction of pre-rearranged Igk genes into their physiological position, the critical rearrangement step was bypassed, thereby generating mice producing B cells simultaneously expressing two different immunoglobulin-kappa light chains. Such 'double-expressing' B cells still underwent monoallelic demethylation at the Igk locus, and the demethylated allele was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 48 publications
0
36
0
1
Order By: Relevance
“…Multiple lines of evidence have linked the generation of ssDNA and the recruitment of AID to the level of transcription (Peters & Storb, 1996; Fukita et al , 1998; Ramiro et al , 2003). AID activity at the IgV genes is thus associated with chromatin features characteristic of actively transcribed loci including DNA hypomethylation, enrichment for the histone modifications H3K4me3 and H3K36me3 and the variant histone H3.3 (Fraenkel et al , 2007; Begum et al , 2012; Aida et al , 2013). However, whether any of these features promotes the activity of AID directly, that is independently of simply promoting transcription, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple lines of evidence have linked the generation of ssDNA and the recruitment of AID to the level of transcription (Peters & Storb, 1996; Fukita et al , 1998; Ramiro et al , 2003). AID activity at the IgV genes is thus associated with chromatin features characteristic of actively transcribed loci including DNA hypomethylation, enrichment for the histone modifications H3K4me3 and H3K36me3 and the variant histone H3.3 (Fraenkel et al , 2007; Begum et al , 2012; Aida et al , 2013). However, whether any of these features promotes the activity of AID directly, that is independently of simply promoting transcription, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…compu-tational predictions based on DNA sequence characteristics or detection of monoallelic expression) of some regions with monoallelic DNA-methylation (2,3,(10)(11)(12)(13)(14)(15)(16), only a few imprinted regions are well characterized in humans, like, for example, the IGF2/H19 region. Furthermore, monoallelic methylation has recently been recognized as very common at non-imprinted loci affecting autosomal genes, regulating, for example, the production of specific antibodies and receptors in the immune system as well as the selection of olfactory receptors (17,18). While monoallelic methylation has been shown to play an important role in the differentiation between tissues, little is known about the specific location of these loci as well as the genome-wide character of monoallelic DNA-methylation.…”
Section: Introductionmentioning
confidence: 99%
“…During B-lineage development, demethylation occurs in a monoallelic fashion prior to the onset of IgK VJ gene rearrangement [34]. Interestingly, recent studies have indicated that the demethylated IgK allele is also selectively targeted by AID [35].…”
Section: Developmental-specific Regulation Of Antigen Receptor Gene Amentioning
confidence: 99%